Dividneds and earnings quality in Poland - Mieczysław Kowerski (e-Finanse: Financial Internet Quarterly, 2013)
The purpose of this article is to show on the example of Warsaw Stock Exchange, Poland (WSE) how in emerging capital markets dividends provide information about earnings quality as measured by their persistence. In the paper the regressions models of future earnings (in years t + 1 and t + 2) were applied on current earnings (in year t), current dividends decision (in year t) and the interaction of current dividend decision and earnings proposed by D. J. Skinner and E. Soltes (2011), using pooled cross - sectional time - series data. A set of 2263 observations coming from the companies listed on the WSE in 1995-2009 was used for the calculation. For estimating the parameters, recursive modeling was used. Specific models were estimated using the heteroskedasticity-corrected general least squares method. It was shown that on the WSE the quality of earnings depends more distinctly on a firm's dividend policy than on the developed markets.
Keywords: G39; 330; quality of earnings; earnings persistence; dividend policy; Warsaw Stock Exchange; performance measurement